PENGARUH EARNINGS MANAGEMENT TERHADAP NILAI PERUSAHAAN: PRAKTIK CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Duwi Nur Romadhon; Barbara Gunawan; Rudy Suryanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2009)
The aim of this research is to examine the effect of earnings management to the firm value: corporate governance practice as moderating variable. The sample of this research was extracted with purposive sampling method. The populations of this research are all of the company which are listed at Indonesian Stock Exchange (IDX). Based on purposive sampling method, 142 companies are considered being the sample in this study. The results of the research show that: ownership manajerial has a significant negative effect on firm value and quality of audit has a significant positive effect on the firm value.